2015
DOI: 10.1007/s00221-015-4254-4
|View full text |Cite
|
Sign up to set email alerts
|

Preserved otolith organ function in caspase-3-deficient mice with impaired horizontal semicircular canal function

Abstract: Genetically engineered mice are valuable models for elucidation of auditory and vestibular pathology. Our goal was to establish a comprehensive vestibular function testing system in mice using: 1) horizontal angular vestibular-ocular reflex (hVOR) to evaluate semicircular canal function, and 2) otolith-ocular reflex (OOR) to evaluate otolith organ function, and to validate the system by characterizing mice with vestibular dysfunction. We used pseudo-off vertical axis rotation (pOVAR) to induce an otolith-only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…A similar impact of genetic background on phenotype has also been observed for Apaf1 −/− and Casp9 −/− mice [1282,1283]. Although Casp3 −/− mice reach adulthood on a C57BL/6 background, they exhibit defects in complex brain functions including attention and (in males) social behavior [1284,1285], as well as ear and vestibular dysfunction including hearing loss [1286][1287][1288][1289][1290], Abnormalities were also seen in the kidney and spleen of aged Casp3 −/− mice [1291]. Survival of Casp3 −/− mice to adulthood in C57BL/6 mice was ascribed to the compensatory activation of CASP7 [1292].…”
Section: Box 4 Impact Of the Apoptosome And Apoptotic Caspases On Healthsupporting
confidence: 60%
“…A similar impact of genetic background on phenotype has also been observed for Apaf1 −/− and Casp9 −/− mice [1282,1283]. Although Casp3 −/− mice reach adulthood on a C57BL/6 background, they exhibit defects in complex brain functions including attention and (in males) social behavior [1284,1285], as well as ear and vestibular dysfunction including hearing loss [1286][1287][1288][1289][1290], Abnormalities were also seen in the kidney and spleen of aged Casp3 −/− mice [1291]. Survival of Casp3 −/− mice to adulthood in C57BL/6 mice was ascribed to the compensatory activation of CASP7 [1292].…”
Section: Box 4 Impact Of the Apoptosome And Apoptotic Caspases On Healthsupporting
confidence: 60%
“…The combination of chemotherapy and pan caspase inhibitor may be beneficial in cancer treatment, especially the promising result from pan caspase inhibitor in clinical trial for hepatitis C, non‐alcoholic steatohepatitis and liver reperfusion injury . However, the activity of caspase 3 often is required for chemotherapy‐, radiotherapy‐ and many targeted therapy‐induced apoptosis and may directly associate the patient's response or survival, to say nothing of the issue with female fertility or development of eye and ear due to lack of caspase 3 . Therefore, targeting another key molecular of “Phoenix Rising” pathway would be more reasonable and safer.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 However, the activity of caspase 3 often is required for chemotherapy-, radiotherapy-and many targeted therapy-induced apoptosis and may directly associate the patient's response or survival, to say nothing of the issue with female fertility or development of eye and ear due to lack of caspase 3. 33 Therefore, targeting another key molecular of "Phoenix Rising" pathway would be more reasonable and safer. Being a potent promoter of cell proliferation, motility, invasion and angiogenesis, 22 the effect of PGE 2 promoting the growth of tumour cells has been reported in variety of cancers, such as colon cancer, lung cancer and ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…We retrieved the same result in Isk-/- mice, years later in a study focused on vestibular neurons in this mutant [ 27 ]. A recent paper by Armstrong and collaborators (2015) [ 28 ] showed that caspase deficient mice with impaired horizontal semicircular canal function and intact otolithic function circle but do not exhibit barrel rolling. Altogether, our results and those of previous studies show that a congenital lack of vestibular function results in a major asymmetry in striatal function, which in turn is causally related to circling.…”
Section: Discussionmentioning
confidence: 99%